Study of donor deferral during blood donation: A single centre teaching hospital study (Bangladesh Journal of Medical Science, 2022)
Background: Safe blood transfusion can be a crucial lifesaving intervention in many clinical situations.For safe blood products donor selection is the first and foremost measure of blood donation.Objective:Aim of the study to determine the incidence and causes for deferral in blood donors.Materials and Methods: This cross-sectional retrospective study was done at Transfusion medicine department in Delta Medical College and Hospital, Bangladesh during 6 months period. In current study data were extracted from the register book and analyzed. Prospective donors were confidentially interviewed and examined and screened for causes of temporary and permanent deferral of blood donation. Data were presented as charts, table and analyzed with Microsoft Excel.Result: A total of 2215 directed donors were studied,of them, 1555 (73.52%) were male and 560 (26.48%) females. Predominantly blood donors belonged to 31–40 years of age group (38.01%). Out of 2115 directed donors, 423 (20%) were deferred. Deferral was significantly more likely in female. The most common cause for deferralwere history of anemia (27.66%). Other causes were antibiotic & medications, high blood pressure, low blood pressure, frequent donation, Positive HBsAg, HCV markers, suspected addiction, and vaccination.Conclusion: Effective measures are required for documenting the deferred donors and appropriate preventive intervention program should be undertaken for prevalent causes of deferrals, like low Hb, Infections with HBV etc. Anemia is the most prevalent reason of temporary deferral for blood donation in this region of Bangladesh. Other reasons were hypertension, hypotension,suspected addiction, vaccination etc.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 645-647